Gut-mediated hypercalcemia in rabbits bearing VX2 carcinoma: new mechanism for tumor-induced hypercalcemia. - Doppelt, S H (1982)
The VX2 carcinoma-bearing rabbit is an animal model for tumor-induced hypercalcemia, thought to be due to increased bone destruction effected by prostaglandin E2. The present experiments suggest that the pathophysiology of the hypercalcemia differs from that previously proposed. Tumor was transplanted intramuscularly into 2.5- to 3-kg male New Zealand White rabbits, which were conditioned to a 1.5% calcium diet and treated with daily subcutaneous injections of dichloromethane diphosphonate (10 mg . kg-1 . day-1), a potent inhibitor of bone resorption, or 0.9% NaCl (2 ml . kg-1 . day -1). The diphosphonate had no significant effect on plasma Ca2+ in either group. After day 31, half the animals of each group were fed a calcium-free diet. This normalized the plasma Ca2+ in each VX2-bearing rabbit within 3 to 4 days but had little effect in control rabbits. In a second series of experiments, VX2-bearing rabbits maintained on standard rabbit chow were treated for 11 days with parenteral indomethacin (30--60 mg/day) or 0.9% NaCl. Although indomethacin normalized the markedly elevated urinary excretion of prostaglandin E2, both treatment groups became severely hypercalcemic. Dietary calcium restriction promptly restored to normal the plasma Ca2+ concentration. In a third series of experiments, rabbits were fed standard rabbit chow and treated with oral indomethacin (40 mg/day) while control-rabbits were pair fed in identical chow. Transplantation of VX2 tumor into both groups caused hypercalcemia. We conclude that the hypercalcemia produced by this tumor strain is indomethacin resistant and dependent on an increase in gastrointestinal calcium absorption, not on skeletal calcium mobilization.